Effect of electroacupuncture on the incidence of acute stroke after embolisation of intracranial aneurysm: study protocol for a single-centre, double-blinded, randomised controlled trial - Zhao, Zi-Jian; Wang, Hang; Ye, Qian; Zhang, Zhen-Feng; Dong, Shi-Yang; Xu, Yi-Fan; Li, Jing-Jin; Yu, Min; Feng, Feng (BMJ open, 2025)
BackgroundElectroacupuncture (EA) is commonly used in clinical settings as a significant method for treating a variety of pain and cerebrovascular disorders. Despite its widespread use, there is limited information on the impact of perioperative EA on postoperative stroke. This study aimed to investigate whether preoperative EA therapy could reduce the occurrence of acute stroke in patients undergoing interventional surgery for intracranial aneurysms.Methods/designThis single-centre, double-blind, placebo-controlled, randomised clinical trial aims to recruit 280 patients undergoing embolisation of intracranial aneurysms under general anaesthesia. Participants will be randomly assigned to either the EA group or sham electroacupuncture (SEA) group. The EA group will receive treatment half an hour before surgery, while the SEA group will receive sham acupuncture. The primary outcome will be the occurrence of acute stroke within 7 days post surgery. Secondary outcomes include the incidence of symptomatic and occult stroke within the same timeframe, the occurrence of cerebral vasospasm during the operation and the number of intraoperative cerebrovascular dissections.Ethics and disseminationThis study has been approved by the Ethics Committee of the First Affiliated Hospital of Nanjing Medical University (2023-SR-538.A1). The study started on 17 May 2024, and it is expected to end on 31 March 2025. The results of our study will be published in peer-reviewed journals.Trial registration numberChiCTR2300076960.